THE EFFECT OF CORONA VIRUS DISAESE (COVID-19) ON JAVA MARRIED TRADITIONS - ishaq, saddam (DE’RECHTSSTAAT, 2022)
The government’s policy in order to accelerate the handling of COVID-19 has a significant impact on people’s culture, including the Javanese wedding culture. A culture that is understood as a tradition that has been believed and carried out hereditary cannot of course be abandoned, even in a pandemic state. However, on the other hand, government policies seem not to take sides with the Javanese marriage culture which tends to have the potential for crowds. The purpose of this study was to determine how the Javanese marriage culture was carried out during the pandemic and to what extent the government regulations provided control over Javanese wedding culture. The research method used is qualitative with the type of empirical research that seeks to describe and analyze events in society. So, get answers to these problems. The results of this study indicate that the rules made by the government seem to have an impact on Javanese wedding culture, so that marriage customs are carried out in two ways: first, do some part and leave the part of the custom that has the potential to cause crowds. The two did not perform any traditional rituals at all and replaced them with other rituals.